Violenza organizzata e appartenenza religiosa. Il caso dell’Isis (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. La religione c’entra? Una premessa culturalista - 2. La violenza organizzata nel mondo e la centralità della guerra siriana - 3. L’ISIS: dall’Iraq alla Siria e recenti sviluppi - 4. Potere o religione? - 5. Chi sono i militanti jihadisti occidentali - 6. Attratti dall’ISIS - 7. Conclusioni.Organized violence and religious affiliation: the case of IsisABSTRACT: This paper seeks to address the crucial issue of organized violence from a cultural perspective analyzing the case of ISIS, tipically considered as religious group. It intends to elaborate some of the key questions of the debate on the links between religion and violence. The religious nature of ISIS will be disputed throughout its birth and expansion during the U.S. invasion of Iraq and the Syrian conflict: more specifically, the paper aims to shed some lights on the grounds underlying the decision of western foreign fighters and Jihadists to join with or refer to a group of fanatics fighting in the faraway land of Syria. The research methodology is based on an interactionist approach on violence in order to avoid focusing on psychopathological (‘they are violent because they are mad’) or ethical-religious aspects (‘they are violent because they are driven by a bad religion’): on the contrary this paper aims to investigate Jihadist violence in its relational and symbolic aspects, as part of a socio-cultural way of life. In the end, the impact of this approach on possible prevention programs will be touched on briefly.
Keywords: Varie